2013
DOI: 10.4269/ajtmh.13-0167
|View full text |Cite
|
Sign up to set email alerts
|

Co-Morbid Infections in Hansen's Disease Patients in the United States: Considerations for Treatment

Abstract: Abstract. 120 patients attending a Hansen's disease public health satellite clinic were evaluated for selected latent co-morbidities, consisting of strongyloidiasis, Chagas disease, hepatitis B, HIV, and tuberculosis, and potential exacerbation by immunosuppressive therapy. Implications for treatment of Hansen's disease are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…4 Co-infections can also pose additional challenges through drug interactions between leprosy multidrug therapy (MDT) and other antimicrobials. 5 The literature on leprosy viral co-infections has focused on HIV, HTLV, hepatitis B, and hepatitis C. [6][7][8][9][10][11] Recently, we have ª 2023 the International Society of Dermatology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Co-infections can also pose additional challenges through drug interactions between leprosy multidrug therapy (MDT) and other antimicrobials. 5 The literature on leprosy viral co-infections has focused on HIV, HTLV, hepatitis B, and hepatitis C. [6][7][8][9][10][11] Recently, we have ª 2023 the International Society of Dermatology.…”
Section: Introductionmentioning
confidence: 99%
“…The literature on leprosy viral co‐infections has focused on HIV, HTLV, hepatitis B, and hepatitis C 6–11 . Recently, we have also seen reports of cases of COVID‐19 in leprosy patients, in a context of strained healthcare services that most severely affected developing countries and delayed progress towards leprosy elimination 12,13 .…”
Section: Introductionmentioning
confidence: 99%
“…Additional articles that reported data on Strongyloides relevant to the use of methotrexate or other immunosuppressive therapy but did not meet study inclusion criteria are reported in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Numerically, more patients experienced dissemination or hyperinfection in the high-dose group (75% vs. 52% P = ns; Table 1). Additional articles that reported data on Strongyloides relevant to the use of methotrexate or other immunosuppressive therapy but did not meet study inclusion criteria are reported in Table 3 [16][17][18][19][20][21].…”
Section: High-compared To Low-dose Mtxmentioning
confidence: 99%
“…1 The unprecedented challenge that persists for leprosy patients is the development of comorbidities during treatment due to reactivation or interaction with other asymptomatic infections. 3 There has been evidence for the presence of co-morbidities such as chronic hepatitis, latent tuberculosis, chronic strongyloidiasis, Chagas' disease, diabetes mellitus and human immunodeficiency virus (HIV). 4 The other co-morbidities include neuropathic ulcers, hearing impairment, mental disorders, restless leg syndrome and renal amyloidosis.…”
Section: Introductionmentioning
confidence: 99%